Zieve Syndrome: A Clinical Triad, or Perchance a Quartet?. (September 2022) - Reyes, Jonathan Vincent M.; Ahmad, Saad; Majeed, Hafsa; Kandoth, Eugenio; Lieber, Joseph J.
Zieve syndrome presents with a triad of hemolytic anemia, unexplained jaundice, and hyperlipidemia secondary to alcohol use/alcohol-induced liver injury, highlighting hemolytic anemia as the hallmark feature. Zieve syndrome is more common than originally perceived as its incidence is estimated to be 1 in 1600 admissions, but its mechanism is still poorly understood. This is a case of a 29-year-old man who developed Zieve syndrome shortly after admission for pancreatitis secondary to alcohol use disorder. Early diagnosis is important to reduce unnecessary tests and interventions. Further studies should be considered to evaluate the association between Zieve syndrome and pancreatitis.